PENERAPAN SISTEM INFORMASI PENJUALAN DAN PEMBELIAN OBAT DI APOTEK X SEMARANG - Toyo, Eleonora Maryeta; Oktaviyani, Triana; Wulandari, Agustina Ratna (Jurnal Farmasi & Sains Indonesia, 2024)
Information systems play an important role in managing and supporting various operational activities, including the process of selling and purchasing drugs. At X Pharmacy Semarang, the system has been computer-based with the use of the SID Apotek PRO application. This application is expected to assist pharmaceutical officers in carrying out the drug sales and purchase system and improve the quality of service to customers. This study aims to understand the drug sales and purchase information system at X Semarang Pharmacy. The methodology used was non-experimental qualitative descriptive research with the research population involving all pharmaceutical officers. The total sampling technique was applied with the entire population being the research sample. The results showed that the information system has not yet supported the drug purchasing process, but can already be used for drug sales. This indicates that the implementation of a drug sales information system helps improve the efficiency of services to patients.